Organic Fertilizer Application on Three Varieties of Irrigated Low-land Rice (Oryza sativa L.) - Prawito, Priyono; Barchia, Faiz; Suhadi, Asman; Widodo; Sumardi (Akta Agrosia, 2024)
Rice is the main staple in Indonesia and the demand for rice production risees along with population growth. Providing organic fertilizer can overcome fluctuations in rice production by increasing nutrient efficiency and being nutrients availability that contribute crop yield increase. This research was carried out in Kaur Regency, Bengkulu Province in September – December 2023. The objective of this research was to investigate the effect of manure on growth and yield of three varieties of irrigated lowland rice. The first experiment was using a Completely Randomized Block Design (CRBD) with 2 factors. The first factor is 3 types of rice varieties, namely Inpari 48, Inpari 32 and Inpari 38. Meanwhile, the second factor is the type of manure, namely cow manure, goat manure and chicken manure. The results of the research showed that in the first experiment it was concluded that there was no real interaction between rice varieties and manure on rice growth and yield. The best rice variety is Inpari 48 which has better growth and yield compared to Inpari 32 and Inpari 38. The application of chicken manure produces better growth and yield of rice and soil chemical properties and agronomic efficiency compared to cow and goat manure. Keywords: efficiency, organic fertilizer, rice varieties